An Extender Kalman Filter-based Induction Machines Faults Detection - Abdelghani Chahmi; Mokhtar Bendjebbar; Bertrand Raison; Mohamed Benbouzid (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper deals with the detection and localization of electrical drives faults, especially those containing induction machines. First, the context of the study is presented and an Extended Kalman Filter is described for induction machines fault detection. Then the modeling procedure under faulty conditions is shown, and the machine diagnosis methods are developed. The proposed diagnosis approach requires only little experimental data, and more importantly it provides efficient simulation tools that allow characterizing faulty behavior.Fault detection uses signal processing techniques in known operating phases (fixed speed), considering and locating malfunctions.